Spatiotemporal Evolution of Droughts and Their Teleconnections with Large-Scale Climate Indices over Guizhou Province in Southwest China - Liying Xiao; Xi Chen; Runrun Zhang; Zhicai Zhang (Water, 2019)
The spatiotemporal evolution of meteorological droughts in Guizhou Province, Southwest China is analyzed based on a new set of the Standardized Precipitation Index series that mainly includes drought events that occurred from 1961 to 2004 at 81 meteorological stations. The cluster analysis shows that the study region can be classified into six homogeneous sub-regions where the drought characteristics and their temporal evolutions are quite different. The trend test and periodicity analysis indicate that Guizhou Province experienced a drier trend, which was most significant in the western parts of the region. It was found that the intensified drought severity was not always coincident with the drier trend but relied on the occurrence of extreme drought events. The trends of drier climate and drought severity were highly coincident with the temporal evolution of the drought periodicities, which were shortened from 1–4 years to less than one year. The shortened drought periodicity was found to be associated principally with a shift of the large-scale dominant climate indices from the North Atlantic Oscillation to the Indian Ocean Dipole after the late 1970s, and variations of the extreme drought events were mostly related to NINO34 in the study region.